(untitled) (Jurnal Teknologi Industri Pertanian, 2023)
Currently, the quality of our environment is consistent decrease by time after time due to economic activities without considering social and environmental dimension. Technically, economic activities can’t be separated from supply chain management (SCM), particularly in agroindustrial. To overcome of this the new approach is needed as a tipping point so that economic and social activities keep going but the loss biodiversity at least can be de reduced. The new approach as circular economy (EC) was sparked by Pearce and Turner in the 90s. The conceptual of this paper provides a comprehensive and systematic review on circular economy topic. Material research is downloaded by several scientific portals through internet network such as Science direct, Emerald insight, Google scholar, Portal garuda, Cross-reef as well as DOAJ which majority before 5 years after published. Most of manuscripts reviewed were published in last five years. The article implements an extension theory for conceptual development of circular economy to explore a main process within supply chain management domain. Basically, the circular economy discuses five principles (i.e closing, slowing, intensifying, narrowing, dematerializing loops) that intersects with SCM process. This article provides a logical framework to spark integration between EC approaches in SCM process. Finally, presented at the end on this article, how EC theory integrating in SCM process in Gayo arabica coffee from Gayo highland, Aceh Province, Indonesia. Keywords: Agroindustrial supply chain, circular economy, Gayo coffee